Implementation of the Substance of Strengthening Labor Relations Based on Presidential Regulation Number 35 of 2022 in Jombang Regency - Masri; Hayat; Suhirmanto (Politeknik Pembangunan Pertanian Malang, 2025)
The implementation of agricultural extension services under the regional autonomy policy has become increasingly disorganized and inconsistent with the SP3K Law. In order to realign the extension function with the requirements of the SP3K Law, Presidential Regulation No. 35 of 2022 on Strengthening the Agricultural Extension Function was introduced. The primary objective of this regulation is to revitalize agricultural advisory services and enhance the effectiveness of extension workers. The aim of this study was to evaluate the execution of Presidential Regulation No. 35 of 2022, which focuses on boosting the Agricultural Extension Function, particularly on the first provision of reinforcing collaborative ties in Jombang Regency, East Java. The study took place between June and July of 2023. The sample for this research encompassed all 21 Agricultural Extension Centers (BPP) located in Jombang Regency. The study's research method involved a descriptive qualitative approach, while the snowball sampling technique was utilized for sampling. Primary data was obtained through direct interviews, and secondary data originated from sources such as the Jombang Regency Program, District Program, Presidential Regulation No. 35 of 2022, journals, theses, and books. Data collection involved techniques such as in-depth interviews, documentation, and literature studies. Descriptive analysis was used for data analysis. The research findings indicate that the implementation of measures to strengthen working relationships has been executed but not fully optimized. The hope is that these findings will serve as input for the local government in improving agricultural extension functions in the future